ADOPTING CONVENTIONAL BUDGET HOTELS INTO MUSLIM-FRIENDLY BUDGET HOTELS: AN EXPLORATORY ANALYSIS - Aam Bastaman; Faridah Hj. Hassan; Ayu Ekasari; Yodfiatfinda Yodfiatfinda (SEAN Institute, 2022)
Budget hotels play an important role in accommodating Muslim youth and low budget travelers who are price-sensitive, as there has been an increasing trend of Muslims traveling across countries. Muslim market is an increasingly attractive market for the tourism industry, thus, providing a big opportunity for budget hotels to offer their services. One of the concerns among the Muslim tourists is whether the hotel is Muslim friendly and could accommodate their halal lifestyle. For example, the availability of facilities for ablution, wet toilet, staffs with a modest dressing code, no pork served, no alcohol, and no adultery entertainment. Meanwhile, budget hotel faces other limitation for Muslim visitors, such as narrow rooms for praying, limited building and land size, resources, etc. The objective of this study is to analyze the appropriateness for conventional budget hotels to adopt into Muslim friendly budget hotels using TOWS analysis. The findings from this study are expected to provide information to indicate the importance of halal tourism knowledge among the conventional budget hotel industry stakeholders to be fully prepared with the opportunities to welcome Muslim visitors. A qualitative approach was employed for this exploratory study. The analyses utilized both primary data through in-depth interviews with selected informants and secondary data from previous research and publications. Moreover, observation was also conducted at several budget hotels within several states in Malaysia. The Muslim-friendly budget hotel model encounters some barriers especially in terms of facilities to support the halal standard.